O niilismo oitocentista expresso no parricídio em Os Irmãos Karamázov - Lima, Antonio Francimar da Silva (2019)
The research aims to establish a Bakhtinian analysis based on the concepts of idea-character, carnavalization and dialogism in The Brothers Karamazov. It is intended to reveal what the ideal characters represent in the novel, that is, how they are characterized, without the simplistic bias of the epics which are based on nineteenth century theological-philosophical nihilism. To this end, a review of the main concepts that intertwine Literature, Society and Theology will be made, given the existing connection in the work under analysis. The 19th century Russian bourgeois and patriarchal society tried to maintain its status quo against Western nihilism, which sought to deconstruct Judeo-Christian traditions; On the one hand were those who wanted to remove ethics based on Christian principles, on the other, those who did not yield to innovation. This suggested the creation of a new man, the übermensch Nietzschiano, and ensured the need for moderate maintenance and renewal. Gradually one realizes that the "new men" were not yet ready to emerge: Ivan Karamázov goes mad at the weight of the guilt of his father's death, since he is the symbol of patricide; Smierdiakov commits suicide when he realizes that his well-crafted plan will not succeed. But religion also needs to be adjusted to the new times, so Alyosha leaves the monastery (bankrupt institution) because she believes it is possible to live and serve like Christ in the real world without the apparatuses of faith.